PENGUATAN KELEMBAGAAN LPQ AT-TAQWA MELALUI KEGIATAN PENGAJIAN PERSERTA DIDIK DAN WALI SANTRI UNTUK MEMBANGUN SINERGITAS PENDIDIKAN AKHLAQ - Guntur Nugroho; Arini Hidayah; Ulfah Dian Indrayani; Yunita Furi Aristasari (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Community service carried out at LPQ At-Taqwa aims to strengthen institutions, increase the number of students and build synergy between guardians and LPQ At-Taqwa to achieve learning objectives. The implementation method of this community service program is to increase children's learning interest through the provision of free uniforms and interesting learning methods. The recitation of students and guardians is packaged in a recitation that presents special missionaries for children. The results of community service activities that have been held with LPQ At-Taqwa are: 1) Increase the number of students to 60 students. 2) Recitation activities with students and guardians. 3) Planning training activities for LPQ management and teacher in developing Quran teaching methods